KOALA – Building Support for Diamond Open Access - Tullney, Marco; Aspaas, Per Pippin (Open Science Talk, 2024)
A discussion with Marco Tullney, initiator of the bottom-up initiative KOALA (Konsortiale Open Access Lösungen Aufbauen, i.e. Establishing Consortial Open Access Solutions). Building upon an established role in the organisation of library consortia that negotiate deals with commercial publishers, Tullney and his colleagues have succeeded to acquire small sums from more than a hundred partner libraries to fund journals and books series. Each funding period lasts for three years, with the consortia covering all legitimate costs of running a publication outlet. So far, ten small to medium sized journals have received funding, as well as two smaller book series. Based on his experience from the German-speaking area, Tullney shares several pieces of advice on how to set up similar funding mechanisms in other regions. He also raises the fundamental question about how to make sure that Diamond OA can grow from its current status as a nieche phenomenon in a limited spectrum of disciplines to becoming a sustainable and attractive model for scholars across all fields. First published online: May 3, 2024.